Espaços construídos, posições ocupadas : história docente de José Calasans Brandão da Silva em Sergipe - Costa, Silvânia Santana (2011)
The present study focus mainly on the teacher José Calasans Brandão da Silva s instructing caring about educational institutions from Sergipe as well as his action as educational technical and member of the Instituto Histórico e Geográfico de Sergipe (Historical and Geographical Institute from Sergipe) . It was used the method biographical-historical which allowed to detail the individual and collective process experienced by José Calasans Brandão da Silva. The categories of analysis used, as a priority, were: representation (CHARTIER, 2009); sociability net (SIRINELLI, 2003); trajectory (BOURDIEU, 1996); Habitus (BOURDIEU, 1990) and social capital (BOURDIEU, 2007). To obtain the information it was carried out documental and bibliographical research, besides interviews. The mainly visited collection stocks for the research were: the Instituto Histórico e Geográfico de Sergipe (IHGS) (Historical and Geographical Institute from Sergipe), the Arquivo Público do Estado de Sergipe (APES) (Public Archive from Sergipe State); the Centro de Educação e Memória Atheneu Sergipense (CEMAS) (Atheneu Sergipense Education and Memory Center), the Instituto de Educação Ruy Barbosa (IERB) (Ruy Barbosa Education Institute), the Universidade Federal de Bahia (UFBA) (Federal University from Bahia), the Núcleo de EstudosBaianos (Studies Center from Bahia) and the Fundação Gilberto Freyre (Gilberto Freyre Foundation). This intellectual collaborated very much with the History from Sergipe and Bahia in the both sides, in the field of his professional practice and in the context of historiography.